CEREBRAL VASCULITIS HISTOPATHOLOGY IN RELAPSING POLYCHONDRITIS. Issue 11 (14th October 2015) - Mbizvo, GK; Ellis, RJB; Michael, BD; Rathi, N; Doran, M; Crooks, D
Abstract : Central nervous system (CNS) involvement in relapsing polychondritis (RPC) is rare and presumed to be the result of either a vasculitic or an encephalitic process, although there is little in the way of histopathological evidence for these. Understanding the underlying pathological process is important because cognitive decline can be halted or reversed with tailored immunosuppression. We describe here the histopathological features of RPC with CNS involvement in a 65-year-old gentleman that presented with rapidly progressive cognitive decline, fevers and ataxia over six weeks. He had bilateral auricular inflammation with cartilage destruction, but relative lobe sparing, ocular inflammation, and a symmetrical small-joint polyarthropathy. The cerebrospinal fluid showed lymphocytic pleocytosis. Diffuse sub-cortical white matter abnormalities were seen on magnetic resonance imaging. A clinical diagnosis of RPC was made on the basis of McAdam criteria. Routinely stained histological brain sections showed scattered foci of vasculitis associated with multinucleated giant cells (MNGC), T-lymphocytes, neutrophils and eosinophils. The leptomeninges were oedematous and thickened by an increase in loose collagenous tissue, vascular proliferation and inflammatory infiltrate of neutrophils, lymphocytes and plasma cells. PAS staining did not reveal any infective organisms. Auricular histology showed central erosion of the cartilage and mild non-specific inflammation of the skin consistent with clinical impression of RPC. In the context of the clinical diagnosis, our findings help further refine the histopathological understanding of RPC involving the CNS, suggesting a vasculitic rather than encephalitic process. Our histology also showed giant perivascular multinucleated cells as part of the vasculitic process, and this not been described before in the literature.